The Procedure of Appoint Judges in the Czech Republic - Sułkowski, Jarosław (Acta Universitatis Lodziensis. Folia Iuridica, 2009)
The analysis of the procedure for appointment of judges shows that it is mostly influenced by the judicial community. Diminishing influence of the executive branch on the consecutive stages of the procedure is also apparent. There are no doubts that a right of access to the public service should be based on the clear and universal principles (i.e. principle of equality). The Czech constitutional law corresponds to European standards. It is worth emphasizing that the constitutionalization above-mentioned principles could give more guarantees to the judicial power.